Controlling the Progression of Curvature in Children and Adolescent Idiopathic Scoliosis Following the Administration of Melatonin, Calcium, and Vitamin D - Alexandru Herdea; Mihai-Codrut Dragomirescu; Alexandru Ulici; Claudiu N. Lungu; Adham Charkaoui (MDPI AG, 2022)
Idiopathic scoliosis affects a severe number of children. Their quality of life and development are also disturbed. Some therapeutic strategies have been developed to control illness progression and to optimize the quality of life. In this perspective, randomized, case-control, interventional study, the impact of using melatonin, calcium, and vitamin D, respectively, on idiopathic scoliosis patients was analyzed. Our preliminary results showed that these drugs positively affected the illness progression quantified by the spine curvature. Patients with idiopathic scoliosis may benefit from a novel treatment by supplementation with vitamin D, calcium, and melatonin.